WORKPLACE SMOKING RESTRICTIONS PROGRAM (Tufts Archival Research Center, 2007)
Report prepared by the Tobacco Institute in 1983 regarding the issue of workplace smoking restrictions. Outlines three major ways in which restrictions are implemented; legislation, litigation and voluntarily. Contains sections on policy questions and recommendations. Recommends that the Institute aggressively oppose all legislative smoking restrictions yet allow employers to make their own voluntary restrictions while trying to influence them against it. Finishes with several appendices addressing specific issues of workplace smoking restrictions.